Endoscopic ultrasound-guided fine-needle biopsy with or without macroscopic on-site evaluation: a randomized controlled noninferiority trial - Mangiavillano, Benedetto; Crinò, Stefano Francesco; Facciorusso, Antonio; Di Matteo, Francesco; Barbera, Carmelo; Larghi, Alberto; Rizzatti, Gianenrico; Carrara, Silvia; Spadaccini, Marco; Auriemma, Francesco; Fabbri, Carlo; Binda, Cecilia; Coluccio, Chiara; Marocchi, Gianmarco; Staiano, Teresa; Conti Bellocchi, Maria Cristina; Bernardoni, Laura; Eusebi, Leonardo Henri; Cirota, Giovanna Grazia; De Nucci, Germana; Stigliano, Serena; Manes, Gianpiero; Bonanno, Giacomo; Ofosu, Andrew; Lamonaca, Laura; Paduano, Danilo; Spatola, Federica; Repici, Alessandro (Endoscopy, 2022)
Background The advantage of using the macroscopic on-site evaluation (MOSE) technique during endoscopic ultrasound-guided fine-needle biopsy (EUS-FNB) performed with 22G Franseen needles has not been investigated. We aimed to compare EUS-FNB with MOSE vs. EUS-FNB performed with three needle passes.Methods This randomized trial involved 10 Italian referral centers. Consecutive patients referred for EUS-FNB of pancreatic or nonpancreatic solid lesions were included in the study and randomized to the two groups. MOSE was performed by gross visualization of the collected material by the endoscopists and considered adequate when a white/yellowish aggregate core longer than 10 mm was retrieved. The primary outcome was diagnostic accuracy. Secondary outcomes were specimen adequacy, number of needle passes, and safety.Results 370 patients with 234 pancreatic lesions (63.2 %) and 136 nonpancreatic lesions (36.8 %) were randomized (190 EUS-FNB with MOSE and 180 with standard EUS-FNB). No statistically significant differences were found between EUS-FNB with MOSE and conventional EUS-FNB in terms of diagnostic accuracy (90.0 % [95 %CI 84.8 %–93.9 %] vs. 87.8 % [95 %CI 82.1 %–92.2 %]; P = 0.49), sample adequacy (93.1 % [95 %CI 88.6 %–96.3 %] vs. 95.5 % [95 %CI 91.4 %–98 %]; P = 0.31), and rate of adverse events (2.6 % vs. 1.1 %; P = 0.28). The median number of passes was significantly lower in the EUS-FNB with MOSE group (1 vs. 3; P < 0.001). Conclusions The accuracy of EUS-FNB with MOSE is noninferior to that of EUS-FNB with three needle passes. MOSE reliably assesses sample adequacy and reduces the number of needle passes required to obtain the diagnosis with a 22G Franseen needle.